Pemeriksaan Gula Darah pada Masayarakat Dusun Buhung Bundang Kecamatan Bontotiro Kabupaten Bulukumba - Islawati Islawati; Asdinar Asdinar; Asriyani Ridwan; Rizky Trisnawati Arwien (Jurnal Pengabdian Masyarakat, 2025)
Diabetes mellitus is a non-communicable disease with increasing prevalence in Indonesia, particularly in rural areas with limited access to healthcare services. The low level of public awareness regarding early detection and healthy lifestyle practices further exacerbates this condition. This community service activity aimed to conduct blood glucose screening and provide health education for elderly residents in Buhung Bundang Hamlet, Bontotiro District, Bulukumba Regency. The method employed in this program was a participatory-educational approach based on the Participatory Action Research (PAR) model. The activity was carried out in three stages: preparation, implementation, and evaluation. Supporting tools included a digital glucometer, a simple screening form, and an educational leaflet titled “Beware of Diabetes! Recognize the Symptoms, Prevent Early.” A total of 20 participants, all elderly residents, were involved in the activity. Results showed that 95% of participants had normal blood glucose levels (<140 mg/dL), while 5% (1 participant) was found to have elevated levels (≥200 mg/dL), indicating potential undiagnosed diabetes mellitus. The educational session and the leaflet effectively improved participants' awareness of diabetes risk factors and preventive measures. This program demonstrated that a participatory and educational approach in community service can be an effective preventive intervention to raise health awareness and promote early detection of non-communicable diseases in rural communities. Similar activities are recommended to be conducted regularly, involving local health volunteers as community-based health educators.